THE EFFECT OF LOW IMPACT AEROBIC EXERCISE ON REDUCING MENOPAUSE SYMPTOMS AT BATU BARA REGENCY 2024 - Yenifebriani Gultom; Novitarum, Lilis; Ginting, Amnita (Jurnal Keperawatan Widya Gantari Indonesia, 2025)
Menopause is a condition that all women will experience. Changes that will occur are reproductive function starting to decline, hormonal, physical and psychological changes. One type of exercise that can reduce or overcome the risk of these changes is low impact aerobic exercise. The benefits of aerobic exercise reduce menopausal symptoms. The aim of this research is to determine the effect of low impact aerobic exercise on reducing menopausal symptoms at Batu Bara Regency 2024. The type of research is a quasi-experiment with a pre-post test design with control group. This research is conducted at Batu Bara Regency from March to April 2024. The sampling technique is purposive sampling with a total of 60 respondents. The instruments are the MRS (Menopause Rating Scale) questionnaire and observation sheet. Gymnastics activities are carried out in twelve meetings four times a week for three weeks with 30 minutes per meeting. Using the Wilcoxon test. The statistical test results obtains p value = 0.001 which shows that there is an influence of Low Impact Aerobic Exercise on Reducing Menopausal Symptoms at Batu Bara Regency 2024. It is hoped that women entering the menopause can do physical activity, especially low impact aerobic exercise, in order to reduce symptoms during menopause.